2020
DOI: 10.3390/su122410688
|View full text |Cite
|
Sign up to set email alerts
|

CSR, Co-Creation and Green Consumer Loyalty: Are Green Banking Initiatives Important? A Moderated Mediation Approach from an Emerging Economy

Abstract: The homogenization of the banking segment has made it difficult for banking institutions to practice the quality of services that are needed in order to retain consumers. Thus, these days, finding ways to increase consumer loyalty—especially green loyalty—has become a challenge for the banking industry around the planet. Research has long acknowledged that corporate social responsibility (CSR) is a strategic concern that could help organizations to increase consumer loyalty. However, the impact of CSR practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 117 publications
(201 reference statements)
4
92
2
3
Order By: Relevance
“…In order to address the situation, the authors adopted another strategy for data collection, and approached the respondents when they were leaving the banks or when they were present outside the ATM premises. The collection of data in such a way is in line with previous researchers [42,43,66].…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…In order to address the situation, the authors adopted another strategy for data collection, and approached the respondents when they were leaving the banks or when they were present outside the ATM premises. The collection of data in such a way is in line with previous researchers [42,43,66].…”
Section: Methodssupporting
confidence: 61%
“…More recently, Moisescu [41] reported that the telecommunication companies implementing sustainable (economic, social, and environmental) policies have better consumer loyalty than those that did not incorporate sustainability at the core of their business objectives. There are different studies on the topic of CSR and customer loyalty in the banking sector that confirm that CSR is positively related to consumer loyalty [34,42,43].…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the study established that CSR communication through social media is directly related to consumer loyalty. This finding also seeks support from the extant literature [12,26,58]. Moreover, the results of the present study also confirmed that e-WOM is a potential mediator between CSR communication of social media and consumer loyalty.…”
Section: Discussionsupporting
confidence: 88%
“…Second, the banking industry of China is very competitive in the present era of digitalization. This stiff competitive environment makes it challenging for every bank to hold its consumers because holding consumers in a tough industry is very difficult [26]. The present study here argues that well-planned CSR communication of a bank on social media enables a bank to shape the behavior of their consumers positively.…”
Section: Introductionmentioning
confidence: 71%